ANALYSIS OF DETERMINANTS OF UNEMPLOYMENT RATE IN INDONESIA - Muhamad Fathul Muin (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2020)
Solving the unemployment issue is one of the best ways to reduce poverty. Through the provision of job opportunities, the poverty rate can be reduced. Therefore, this research explores the factors that influence the unemployment rate across 34 provinces over the 2015-2018 period using the panel regression technique. The variable used consisting of economic growth, the percentage of people with IT competence, and the average school duration. This study indicates that the unemployment rate can be reduced by increasing the average school duration. Meanwhile, the level of economic growth and the proportion of people with IT competence have an insignificant influence on Indonesia's unemployment rate. Based on these findings, the government needs to ensure that every resident in its territory can receive an adequate education.